Vagus Nerve Stimulation Attenuates Acute Skeletal Muscle Injury Induced by Hepatic Ischemia/Reperfusion Injury in Rats - Xin, Ying; Zhang, Yifeng; Deng, Simin; Hu, Xinqun (Frontiers in Pharmacology, 2022)
Vagus nerve stimulation (VNS) has a protective effect on distal organ injury after ischemia/reperfusion (I/R) injury. We aimed to investigate the protective efficacy of VNS on hepatic I/R injury-induced acute skeletal muscle injury and explore its underlying mechanisms. To test this hypothesis, male Sprague-Dawley rats were randomly divided into three groups: sham group (sham operation, n = 6); I/R group (hepatic I/R with sham VNS, n = 6); and VNS group (hepatic I/R with VNS, n = 6). A hepatic I/R injury model was prepared by inducing hepatic ischemia for 1 h (70%) followed by hepatic reperfusion for 6 h. VNS was performed during the entire hepatic I/R process. Tissue and blood samples were collected at the end of the experiment for biochemical assays, molecular biological preparations, and histological examination. Our results showed that throughout the hepatic I/R process, VNS significantly reduced inflammation, oxidative stress, and apoptosis, while significantly increasing the protein levels of silent information regulator 1 (SIRT1) and decreasing the levels of acetylated forkhead box O1 and Ac-p53, in the skeletal muscle. These data suggest that VNS can alleviate hepatic I/R injury-induced acute skeletal muscle injury by suppressing inflammation, oxidative stress, and apoptosis, potentially via the SIRT1 pathway.